PROFESIONALISASI GURU BAHASA INGGRIS SEKOLAH YAYASAN PENDIDIKAN JAYAWIJAYA MENUJU SEKOLAH BERTARAF INTERNASIONAL: Sebuah Analisis Reflektif dalam Perspektif Psikologi - Supriyono Supriyono (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2015)
This study aims at describing pilot projects to increase teachers ’ professionalism in English proficiency. Pilot project was conducted by Yayasan Pendidikan Jayawijaya, Papua regarding efforts to increase school quality management from national into international qualification. Reflective analysis using qualitative approach was used for analysis. This study revealed that strategies to conduct the policy asserted psychological perspectives focusing and maintaining motivation, expectation and andragogy implementation. Teachers ’ problems were approached through constructive relation. The pilot project that initially was administered for English teachers, has been implemented successfully for all teachers at the Yayasan.